Developmental disorders among Norwegian-born children with immigrant parents - Hansen TM; Qureshi S; Gele A; Hauge LJ; Biele GP; Surén P; Kjøllesdal M (BMC, 2023)
Abstract Background Risk of being diagnosed with different developmental disorders is found to vary with immigrant background. Knowledge about such differences in Norway are a starting point for equity in health services quality, and for early identification and prevention. Our objective was to assess the risk of receiving diagnoses of developmental disorders among children born in Norway (2006-2017) to two or one immigrant parent compared to children with two Norwegian-born parents. Methods Information on developmental disorders was from the Norwegian Patient Register (NPR) and information on immigrant background, parental country of origin, parental education, and household income from Statistics Norway. We estimated hazard ratios (HR) with Cox proportional hazard regressions. With children with Norwegian background as reference category, we estimated HRs for immigration background and region of origin. All analyses were adjusted for sex, year of birth, parental education, and household income. Results Children with two immigrant parents had a lower risk of receiving any developmental disorder diagnosis [HR 0.80 (95% CI 0.77, 0.82)] than children with Norwegian background, and lower risk of being diagnosed with attention deficit hyperactivity disorder (ADHD) diagnosis [HR 0.24 (95% CI 0.22, 0.27)], learning difficulties diagnosis [HR 0.39 (95% CI 0.33, 0.47)], and behavioral and emotional disorders [HR 0.52 (95% CI 0.49, 0.55)]. Children with immigrant parents had higher hazard than Norwegian background children of autism spectrum disorder (ASD) [HR 2.21 (95% CI 2.04, 2.39)], mental retardation [HR 1.84 (95% CI 1.64, 2.07)], language disorders [HR 1.30 (95% CI 1.20, 1.40)], and unspecified developmental disorders [HR 1.22 (95% CI 1.17, 1.28)]. Children with only one immigrant parent had lower risk of diagnoses than children of two immigrants. Conclusion Risk of receiving a diagnosis of various developmental disorders varied substantially by immigrant background. Understanding the underlying mechanisms of these differences is warranted to ensure equity in health services and timely intervention.